A study on safety culture : the perception and variation among the emergency medical services in Kelantan - Saad, Shahzuwaty (2015)
Introduction: In any industry, most safety management is about minimizing accidents to workers, although some sectors such as transportation, nuclear power generation or food production, the public is also at risk. However, in healthcare industry it is not only patients who are injured, staff can be affected too. The healthcare providers are regularly exposed to hazards such as verbal and physical assaults by both colleagues and patients. These health and safety risks suggest that the health care work environment is a potentially unsafe workplace that negatively impacts health care providers. Neal and Griffin (2004) had explained in their study that safety climate do influence worker’s knowledge and motivation, which in turns impacts on their safety behaviors and finally on safety outcomes. The aim of this study was to measure the Emergency Medical Services safety culture. To date, no nationwide safety survey has been conducted in Malaysia on Emergency Medical Services personnel. It also can make a benchmark result against international data which have been widely assessed in United States of America, United Kingdom and some ASEAN countries and at the same time can guide a unit-based, integrated and risk management strategy. Method: We conducted across-sectional study involving 10 hospitals in Kelantan that offer Emergency Medical Services and it took fourteen months period. We administered a Malay version of EMS Safety Attitude Questionnaire (EMS-SAQ), a survey instrument measuring dimension of workplace safety culture. All Emergency Medical Team (EMT) staff in Emergency Department at the time of data collection were included in the study. Those were doctors, paramedics, staff nurses, medical assistants, attendants and drivers. We determined the variation in safety culture score in all the institutions and also the association between socio demographic factors and level of safety culture practice among EMS in Kelantan. Results: We received 319 completed surveys from 10 hospitals in Kelantan. The majority of respondent were male (55.8%) with mean age of respondent was 35.2 year old. Majority of the respondents were Malays (93.7%) and predominantly staff nurse and medical assistant followed by doctors. Mean years of services in EMS was 10.9 years. There was wide variation in safety culture score across the EMS agencies in Kelantan but not statistically significant in term of safety culture score between university hospital and public tertiary hospital in Kelantan and safety culture score between hospitals with and without Emergency physician in each safety culture domain that have been examined. Conclusion: Patient safety is an important healthcare issue in all countries and should be a continuous process. It should be a top strategic priority for EMS as a frontline staff. The results in this study have shown that within same state, there were variations in perception on safety culture among the Emergency Medical Services in Kelantan. However, for a better result, the involvement of other healthcare workers or emergency department staff from other hospital throughout Malaysia is needed for a larger study to ensure a more comprehensive data.